The UK EndoVascular Aneurysm Repair (EVAR) randomised controlled trials: long-term follow-up and cost-effectiveness analysis - Rajesh Patel (Health Technology Assessment, 2018)
Background: Short-term survival benefits of endovascular aneurysm repair (EVAR) compared with open repair (OR) of intact abdominal aortic aneurysms have been shown in randomised trials, but this early survival benefit is soon lost. Survival benefit of EVAR was unclear at follow-up to 10 years. Objective: To assess the long-term efficacy of EVAR against OR in patients deemed fit and suitable for both procedures (EVAR trial 1; EVAR-1); and against no intervention in patients unfit for OR (EVAR trial 2; EVAR-2). To appraise the long-term significance of type II endoleak and define criteria for intervention. Design: Two national, multicentre randomised controlled trials: EVAR-1 and EVAR-2. Setting: Patients were recruited from 37 hospitals in the UK between 1 September 1999 and 31 August 2004. Participants: Men and women aged ≥ 60 years with an aneurysm of ≥ 5.5 cm (as identified by computed tomography scanning), anatomically suitable and fit for OR were randomly assigned 1 : 1 to either EVAR (n = 626) or OR (n = 626) in EVAR-1 using computer-generated sequences at the trial hub. Patients considered unfit were randomly assigned to EVAR (n = 197) or no intervention (n = 207) in EVAR-2. There was no blinding. Interventions: EVAR, OR or no intervention. Main outcome measures: The primary end points were total and aneurysm-related mortality until mid-2015 for both trials. Secondary outcomes for EVAR-1 were reinterventions, costs and cost-effectiveness. Results: In EVAR-1, over a mean of 12.7 years (standard deviation 1.5 years; maximum 15.8 years), we recorded 9.3 deaths per 100 person-years in the EVAR group and 8.9 deaths per 100 person-years in the OR group [adjusted hazard ratio (HR) 1.11, 95% confidence interval (CI) 0.97 to 1.27; p = 0.14]. At 0–6 months after randomisation, patients in the EVAR group had a lower mortality (adjusted HR 0.61, 95% CI 0.37 to 1.02 for total mortality; HR 0.47, 95% CI 0.23 to 0.93 for aneurysm-related mortality; p = 0.031), but beyond 8 years of follow-up patients in the OR group had a significantly lower mortality (adjusted HR 1.25, 95% CI 1.00 to 1.56, p = 0.048 for total mortality; HR 5.82, 95% CI 1.64 to 20.65, p = 0.0064 for aneurysm-related mortality). The increased aneurysm-related mortality in the EVAR group after 8 years was mainly attributable to secondary aneurysm sac rupture, with increased cancer mortality also observed in the EVAR group. Overall, aneurysm reintervention rates were higher in the EVAR group than in the OR group, 4.1 and 1.7 per 100 person-years, respectively (p < 0.001), with reinterventions occurring throughout follow-up. The mean difference in costs over 14 years was £3798 (95% CI £2338 to £5258). Economic modelling based on the outcomes of the EVAR-1 trial showed that the cost per quality-adjusted life-year gained over the patient’s lifetime exceeds conventional thresholds used in the UK. In EVAR-2, patients died at the same rate in both groups, but there was suggestion of lower aneurysm mortality in those who actually underwent EVAR. Type II endoleak itself is not associated with a higher rate of mortality. Limitations: Devices used were implanted between 1999 and 2004. Newer devices might have better results. Later follow-up imaging declined, particularly for OR patients. Methodology to capture reinterventions changed mainly to record linkage through the Hospital Episode Statistics administrative data set from 2009. Conclusions: EVAR has an early survival benefit but an inferior late survival benefit compared with OR, which needs to be addressed by lifelong surveillance of EVAR and reintervention if necessary. EVAR does not prolong life in patients unfit for OR. Type II endoleak alone is relatively benign. Future work: To find easier ways to monitor sac expansion to trigger timely reintervention. Trial registration: Current Controlled Trials ISRCTN55703451. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and the results will be published in full in Health Technology Assessment; Vol. 22, No. 5. See the NIHR Journals Library website for further project information.